Progressive Supranuclear Palsy: A Crucial Co-occurrence in Normal Pressure Hydrocephalus or an Etiology of Hydrocephalic Presentation? - Halil Onder (Indian Journal of Neurosurgery)
Co-occurrences of neurodegenerative diseases in normal pressure hydrocephalus (NPH) is a remarkable topic of discussion, which has been mentioned in recent studies and it was also emphasized by the International Society for Hydrocephalus and Cerebrospinal Fluid Disorder. In this report, I illustrate two remarkable cases which were initially diagnosed with idiopathic normal pressure hydrocephalus (iNPH) and ventriculoperitoneal (VP) shunt surgery was performed, which yielded significant improvement in the clinic of both patients in the short-term period. However, in the long-term follow-up, both of them deteriorated, and re-evaluation of the neurological examination and neuroimaging data yielded the full clinical picture of progressive supranuclear palsy (PSP). Via the illustration of these cases and related literature data, I rediscuss some related hypotheses about the co-occurrence of these two conditions of hydrocephalus and PSP. I also suggest some distinct discussions to be clarified in future studies.